Slovenia : Pilot Diagnostic Review of Governance of the Banking Sector - World Bank (Washington, DC, 2013)
The financial crises of the late 1990s in East Asia and Eastern Europe, as well as the recent corporate governance scandals in Europe and America, have highlighted the need for strong corporate governance in ensuring a sound and stable financial sector. The governance practices of banks are important because banks accept deposits from the public, whose funds the government has an implicit (and often an explicit) obligation to protect. Banks are also subject to information asymmetries and high leverage, both of which make banks vulnerable to a sudden run on deposits where public confidence fails. The Slovenian bank governance review has three objectives to: 1) conduct a review of the Slovenian bank governance framework, 2) make recommendations on provisions that would help to strengthen the governance structure of banks in Slovenia, and 3) refine the good practices developed for the pilot banking governance review program. In addition, the international community has encouraged the strengthening of governance in the banking sector. The Slovenian banking sector has successfully weathered the financial crisis seen in other countries in 1997-1998, and has improved its stability. However some shortcomings in bank governance remain. The government remains the dominant owner of banks in Slovenia.